Pengaruh Pendekatan Pembelajaran Kontekstual Terhadap Maharah Qira’ah Siswa MTs Soebono Mantofani - Evi Oktaviani; Lalah Alawiyah; Iman Matin (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2026)
This study was motivated by the low reading skills (maharah qira’ah) of students and the importance of using a meaningful learning approach. It aimed to examine the effect of the contextual teaching approach on improving the reading skills of ninth-grade students at Madrasah Tsanawiyah Soebono Mantofani and to explore its implementation in the learning process. The research employed a mixed-method design with an explanatory sequential approach, in which quantitative data were first collected through pretests and posttests and analyzed using the Wilcoxon test, followed by qualitative data obtained through classroom observations, teacher interviews, and student questionnaires to strengthen and explain the quantitative findings. The participants consisted of 42 ninth-grade students divided into experimental and control groups. The quantitative results indicated a significant improvement in students’ reading skills after the implementation of the contextual teaching approach, with an Asymp. Sig value of 0.000 < 0.05, supported by the N-Gain results showing that 81% of students were in the high improvement category and 19% in the moderate category. The mean score of the experimental class increased more substantially than that of the control class, leading to the rejection of the null hypothesis and acceptance of the alternative hypothesis. Qualitative findings revealed that the success of contextual learning was influenced by high student motivation, the relevance of learning materials to real-life contexts, the use of text and image-based instructional media, an interactive classroom environment, and the accommodation of individual differences in students’ vocabulary and reading experience. Therefore, the contextual teaching approach was proven effective in enhancing reading comprehension and making learning more meaningful, practical, and oriented toward deeper understanding.